Imperfect information, wage formation, and the employability of the unemployed - Stefan Eriksson (Institute for Labour Market Policy Evaluation (IFAU), 2002)
This paper considers the optimal hiring strategy of a firm that is unable to observe the productive abilities of all its applicants. Whom the firm considers as hireable, will depend crucially on the extent to which the firm can use its wage setting to mirror productivity differences. However, when setting its wages the firm has to consider other factors as well, e.g. turnover, that may make it optimal not to set wages that fully reflect productivity differences. Instead, it may be optimal to avoid hiring workers that have certain characteristics; i.e. to use a discriminatory hiring strategy. In the paper it is shown that discrimination based on employment status is an equilibrium hiring strategy even when the firm is free to set different wages for workers with different expected productivities. It is also shown that if all firms use such hiring procedures this will have strong implications for the aggregate economy and welfare.
Keywords: E24; J64; J71; 330; Hiring; imperfect information; discrimination; employed job seekers; efficiency wages; turnover; unemployment; welfare; policy